Prevalence and clinical profile of metabolic syndrome amongst essential hypertensive patients at Navi Mumbai, India - Pakhale, Ketan L.; Pakhale, Rajshree K.; Bhate, Archana R.; More, Shyam C. (International Journal Of Community Medicine And Public Health, 2020)
Background: The prevalence of metabolic syndrome (MetS), a pathophysiological and asymptomatic state of numerous complications has been documented in various recent studies worldwide. Inadequate data are available highlighting the magnitude of MetS in country like India whose major health problem has been infectious disease rather than non-communicable disease like hypertension. The aim of the present study was to determine the prevalence of MetS in essential hypertensive patients using the criteria of the National Cholesterol Education Program's adult treatment panel III. Methods: A cross-sectional study was conducted on 80 hypertensive patients above the age of 40 years at OPD of School of Medicine, D. Y. Patil Deemed to be University, Navi Mumbai. Various anthropometric, biochemical, echocardiographic and ophthalmoscopic data were recorded from the patients using standardized laboratory protocols. Results: Our studies revealed a prevalence rate of 17.5% of MetS in patients with essential hypertension. Triglyceride level abnormality was found to be more prevalent in our cohort whereas 17% of the total population displayed central obesity. Elevated blood sugar levels were exhibited by 85% of the population revealing the susceptibility towards diabetic condition. Echocardiographic data revealed complications such as concentric left ventricular hypertrophy, global hypokinesia and low heart’s ejection fraction ability in some subjects. Our ophthalmoscopic data is suggestive of hypertension related eye complications in half of our study population. Conclusions: Collectively our results demonstrate an increased prevalence of MetS, therefore early detection and management of MetS in individuals with high risk can aid in preventing many complications in patients.